Recent migration in Israel: measures and impact - Berthomiére, William (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article is a contribution to the knowledge on the migratory results stemming from the collapse of the communist bloc. Since 1989, more than 650.000 Jews have left the Former USSR for Israel. Thus, Israel is became one of the major countries who have felt the effects of this important geopolitical event. So, in this contribution, we will try to expose, with some results of research, the patterns of this migration and to answer the inherent questions in this kind of problematic: how Israel manages with this new migration, what are the effects of this migration for this area so tormented and debated... Also, we will put accent on the links established between Israel and FSU with the support of the migrants networks. In final, we will try to replace this movement in the new Israeli context of migrations in which we can see an integration of the state in the European migration system with the new trend of foreign workers and the development of an illegal population.